Development of nanocomposite hydrogel using citrate-containing amorphous calcium phosphate and gelatin methacrylate - Indurkar, Abhishek; Rubenis, Kristaps; Boccaccini, Aldo R.; Locs, Janis (Frontiers in Bioengineering and Biotechnology, 2024)
Nanocomposite hydrogels are suitable in bone tissue engineering due to their resemblance with the extracellular matrix, ability to match complex geometries, and ability to provide a framework for cell attachment and proliferation. The nanocomposite hydrogel comprises organic and inorganic counterparts. Gelatin methacrylate (GELMA) is an extensively used organic biomaterial in tissue engineering due to its excellent biocompatibility, biodegradability, and bioactivity. The photo-crosslinking of GELMA presents a challenge when aiming to create thicker nanocomposite hydrogels due to opacity induced by fillers, which obstructs the penetration of ultraviolet (UV) light. Therefore, using a chemical crosslinking approach, we have developed nanocomposite GELMA hydrogel in this study by incorporating citrate-containing amorphous calcium phosphate (ACP_CIT). Ammonium persulfate (APS) and Tetramethylethylenediamine (TEMED) were deployed to crosslink the methacrylate group of GELMA. The oscillatory shear tests have confirmed that crosslinking enhances both storage (G′) and loss modulus (G″) of GELMA. Subsequently, incorporation of ACP_CIT in GELMA hydrogel shows further enhancement in G′ and G″ values. In vitro analysis of the developed hydrogels revealed that chemical crosslinking and incorporation of ACP_CIT do not compromise the cytocompatibility of the GELMA. Hence, for developing nanocomposite GELMA hydrogels employing APS/TEMED crosslinking emerges as a promising alternative to photo-crosslinking.